An ontology for software engineering education - Thong, Chee Ling; Jusoh, Yusmadi Yah; Adbullah, Rusli; Alwi, Nor Hayati (The Institute of Education Sciences (IES), 2013)
Software agents communicate using ontology. It is important to build an ontology for specific domain such as Software Engineering Education. Building an ontology from scratch is not only hard, but also incur much time and cost. This study aims to propose an ontology through adaptation of the existing ontology which is originally built based on a qualification framework.